Considering gender in research: an ethics and standards toolkit - Faas, Simone; Makhija, Simrin; Bryan, Elizabeth; Go, Ara; Malapit, Hazel J. (CGIAR GENDER Impact Platform, 2022)
This gender research ethics and standards toolkit is a ‘living’ document that will provide guidance, recommendations and resources on the gender-relevant ethical considerations for research involving human subjects. The toolkit aligns with the CGIAR’s core ethical values outlined in the CGIAR Ethics Framework of (1) integrity, (2) dignity and respect, (3) sustainability, (4) excellence and innovation, and (5) partnership. This toolkit aims to support CGIAR researchers and their research partners conducting research on human subjects—whether via surveys, interviews, focus group discussions, participant observations, multistakeholder dialogues, or participatory action and learning—in accordance with the CGIAR Research Ethics Code (CGIAR System Management Office 2020).